Microsurgical anatomy of the anterior commissure through the anterior interhemispheric transcallosal approach to the third ventricle: An anatomical and morphological study - Aydın, Seçkin; Esen Aydın, Ayşegül; Tanriöver, Necmettin (Journal of Surgery and Medicine, 2020)
Aim: The third ventricle is a funnel-shaped cavity located deep in the brain and difficult to access with surgical approach. The anterior commissure is an anatomical structure located on the anterior wall of the third ventricle. This study aimed to demonstrate the use of the anterior interhemispheric transcallosal approaches to access the third ventricle, evaluate the microsurgical anatomy of the anterior commissure and investigate the morphological features of this region. Methods: Eleven cadaveric brain specimens were dissected using microsurgical tools. Different anterior interhemispheric routes to the third ventricle were demonstrated, and stepwise dissections were performed to expose the limbs of the anterior commissure. Morphological measurements of the anterior commissure and the third ventricle were carried out. Results: The anterior limb of the anterior commissure extends towards the anterior perforating substance, olfactory bulb, anterior olfactory nucleus and the orbitofrontal cortex. The posterior limb extends from the basal part of the caudate nucleus, passes below the substantia innominata and courses through the basal part of the putamen. It constitutes the major component of the anterior commissure and is composed of temporal and occipital fibers. The mean length of the anterior commissure body was 16.2 ± 4.2 (range 9.7–24.2) mm, while the mean width was 4.3 ± 0.7 (range 2.8–5.1) mm. Conclusion: A better understanding of the microsurgical anatomy and morphometric features of the third ventricle and anterior commissure increases the success of surgical interventions and prevents possible complications in this region.